INTEGRASI LINGUISTIK TERAPAN DENGAN KURIKULUM BAHASA ARAB: Perspektif Linguistik Terapan dalam Reformasi Kurikulum Bahasa Arab - Agus Ikhsanudin; Asep Parida; Nurlaela; Iis Susiawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This paper explores the integration of applied linguistics with the Arabic language curriculum as a strategic approach to improving the quality and relevance of Arabic education in Indonesia. Arabic, as a language of religion, science, and culture, requires a curriculum that not only emphasizes grammatical mastery but also communicative competence and contextual understanding. However, Arabic instruction in many institutions remains traditional, focusing on classical grammar without connecting theory to real-life communication. Applied linguistics provides a practical and functional framework for bridging this gap by linking linguistic theory to language teaching, curriculum design, assessment, and educational technology. The study highlights four main aspects of integration: (1) the role of applied linguistics in curriculum development through needs analysis, error analysis, and contrastive studies; (2) strategies for implementation, including communicative and functional approaches, linguistic-based material development, evaluation through error analysis, and the use of digital linguistic tools; (3) examples of practical application at schools, universities, and language centers where task-based and research-based learning models are adopted; and (4) challenges and solutions such as uneven teacher competence, limited data-driven materials, resistance to innovation, and technological constraints. By synthesizing theoretical and practical perspectives, this paper argues that integrating applied linguistics can make Arabic learning more scientific, student-centered, and responsive to sociocultural contexts. It promotes a curriculum grounded in real learner needs and communicative goals, encouraging collaboration between linguists, educators, and policymakers. The integration not only strengthens linguistic competence but also fosters adaptive, interactive, and meaningful learning in the digital era. Consequently, applied linguistics serves as a vital instrument for reforming Arabic language education and developing learners who can use Arabic effectively and contextually in academic and everyday communication.